2016
DOI: 10.1177/1545968316680493
|View full text |Cite
|
Sign up to set email alerts
|

Does Task-Specific Training Improve Upper Limb Performance in Daily Life Poststroke?

Abstract: Background A common assumption is that changes in upper limb (UL) capacity, or what an individual is capable of doing, translate to improved UL performance in daily life, or what an individual actually does. This assumption should be explicitly tested for individuals with UL paresis post-stroke. Objective To examine changes in UL performance after an intensive, individualized, progressive, task-specific UL intervention for individuals at least 6 months post-stroke. Methods Secondary analysis on 78 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(122 citation statements)
references
References 53 publications
7
110
3
2
Order By: Relevance
“…Participant demographics, and MAL-AOU and use ratio values (Table 1) were not different from the trial cohort. 7,8 Consistent with previous reports 5 , the MAL and use ratio were moderately associated at baseline (r=0.31, 95% CI [0.07, 0.51], p = 0.014) and post-intervention (r = 0.52, 95% CI [0.32, 0.68], p < 0.001).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Participant demographics, and MAL-AOU and use ratio values (Table 1) were not different from the trial cohort. 7,8 Consistent with previous reports 5 , the MAL and use ratio were moderately associated at baseline (r=0.31, 95% CI [0.07, 0.51], p = 0.014) and post-intervention (r = 0.52, 95% CI [0.32, 0.68], p < 0.001).…”
Section: Resultssupporting
confidence: 88%
“…Participants wore the accelerometers for 24 hours at baseline and again post-intervention during all daily activities. 8 The variable of interest for this comparison was the use ratio, an established metric of UL performance in daily life. 4,9 The use ratio quantifies the amount of time the paretic UL is active relative to the non-paretic UL and ranges from 0–1.…”
Section: Methodsmentioning
confidence: 99%
“…28 The six metrics are indices of unilateral and bilateral activity, quantifying intensity, magnitude, contributions from each limb, and variability throughout the day. 28 The lack of change in performance occurred in spite of formal bi-weekly and informal, per-session discussions with each participant about how they might incorporate use of the hand and arm into daily activities. Figure 3 shows group data from one metric, the activity (or use) ratio.…”
Section: Strokementioning
confidence: 99%
“…Repetition is necessary in order to progress to the next highest level of difficulty in the learning of motor control. In recent work [40-41], the number of repetitions was reported, respectively, for 13.6 hrs, 20.0hrs, and 26.3hrs of therapy for mildly/moderately impaired chronic stroke survivors, along with the findings that no increased use of the impaired limb was recorded at home and there was no significant difference in this across the three groups of different dosage (hours of treatment). In contrast, and though no ‘home use measure’ was used, other work [29,42] has shown that even more impaired (moderately/severely) chronic stroke survivors could exhibit recovery of coordinated limb movements and activities of daily living (e.g., pick up the knife and fork and cut the meet).…”
Section: Elements Of Training That Are Important For Motor Learning Amentioning
confidence: 99%